Cognitive decline in patients with essential tremor - M. M. Ermakova; Z. A. Zalyalova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2023)
Essential tremor (ET) is a heterogeneous disease with a high prevalence and disability. Traditionally, the disease was considered benign with the presence of tremor, the severity of which increases during the observation period. The severity of trembling varies widely from mild, not requiring therapy, to disabling. That is making difficulties to assess the prevalence of the disease. However, disability in patients with ET can occur not only due to the severity of tremor.The underestimated side of the disease, despite a long history of study, remains non-motor manifestations, including cognitive decline. Cognitive decline in essential tremor, compared with the general population, has a greater risk of transformation into dementia. In patients with ET, in comparison with other cognitive domains, executive functions are predominantly affected. Patients are also characterized by low awareness and concern about changes in intelligence. In the study of the brain using voxel morphometry, a heterogeneous group of changes that contradict each other was revealed. Most often, a change in the density of the cortex of different parts of the brain is detected in comparison with the control group. The most affected area of the brain is the precuneus. This may explain the executive dysfunction in patients and highlight the likely neurodegenerative nature of essential tremor. The absence of preventive therapy, the high incidence of changes in intelligence emphasizes the need for close monitoring of patients.